RELEVANCY OF INDOOR TEMPERATURE AND FENG SHUI LUO PAN COMPASS: THE CASE OF DOMESTIC BUILDINGS IN SURABAYA, INDONESIA - Juan Hogianto; Christina E. Mediastika (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
This paper reports an investigation of the scientific justification of room temperature and the beliefs on Luo Pan Compass; a part of Feng Shui wisdom. The compass is a rule of thumb on the placement of a particular room within a house to achieve indoor comfort and occupants’ well-being based on house orientation to the wind direction. The study was conducted in a quantitative method consists of field measurements and questionnaire survey. The result was to be consulted with indoor temperature comfort standard and to the Luo Pan Compass. Eight houses were selected in a purposive method. The investigation showed that the indoor temperature of seven out of eight studied houses were not within the standard. It was in good agreement with the respondents’ opinions. The finding of this study may be referred by building designers that Luo Pan Compass is relevant to the temperature comfort level of the indoor environment.